Haemathological and histological evaluation of African catfish Clarias gariepinus following acute exposure to Methanolic extract of Khaya senegalensis (Research in Agriculture Livestock and Fisheries, 2015)
Haematological and histopatholoical effects of methanolic extract of K. senegalensis leaves was investigated on Clarias gariepinus over a period of 96h exposure. The median lethal concentration of the extract was 199.69mg/L. The extract caused decreased in total erythrocytes (TEC) and Packed Cell volume (PCV) respectively and increased of total leukocytes (TLC). Histopathological lesions in the liver, cytoplasmic degeneration, less intracellular space, mild necrosis, sinusoidal blood congestion and marked blood congestion in hepathocytes were recorded. However the severity but not the type of lesions was concentration-dependent. Though, the degree of tissue change (DTC) varied with the methonolic extract used. There was significant association (P